Impresi Karyawan terhadap Penggunaan Aplikasi Artificial Intelligence Elsa Speak pada PT Elang Mahkota Teknologi - Saputri, Tri Bata Biru; Andrian, Pieter (Politeknik Negeri FakFak, 2024)
Foreign language competence makes the main capital in carrying out work. Someone with foreign language skills, especially English, can negotiate and give presentations more fluently. Along with this, the opportunity to build a network of connections will be extended, As a result, business opportunities are easier to achieve. Elsa (English Learning Speech Assistant) is an English learning application that applies artificial intelligence and speech recognition. This learning application focuses on the speaking ability. The purpose of the research is to find out the employee's impression of the use of Elsa Speak on PT Elang Mahkota Teknologi. This research is a descriptive research with qualitative and quantitative approaches. The research subjects were 21 employees. They are the division representatives at PT Elang Mahkota Teknologi. The results of the research shows that employees have a positive response to the presence of Elsa Speak to improve speaking skills. The convenience and practicality presented by Elsa Speak is very suitable for the learners. They can learns anytime and anywhere. They agree that the features presented by Elsa have a good influence on speaking ability. In addition, the individualized curriculum is able to adjust to the weaknesses of each learner.